Recurrence of Primary Sclerosing Cholangitis After Liver Transplant in Children: An International Observational Study. Issue 4 (9th September 2021) - Martinez, Mercedes; Perito, Emily R.; Valentino, Pamela; Mack, Cara L; Aumar, Madeleine; Broderick, Annemarie; Draijer, Laura G.; Fagundes, Eleonora D.T.; Furuya, Katryn N.; Gupta, Nitika; Horslen, Simon; Jonas, Maureen M.; et al.
Abstract : Background and Aims: Recurrent primary sclerosing cholangitis (rPSC) following liver transplant (LT) has a negative impact on graft and patient survival; little is known about risk factors for rPSC or disease course in children. Approach and Results: We retrospectively evaluated risk factors for rPSC in 140 children from the Pediatric PSC Consortium, a multicenter international registry. Recipients underwent LT for PSC and had >90 days of follow‐up. The primary outcome, rPSC, was defined using Graziadei criteria. Median follow‐up after LT was 3 years (interquartile range 1.1‐6.1). rPSC occurred in 36 children, representing 10% and 27% of the subjects at 2 years and 5 years following LT, respectively. Subjects with rPSC were younger at LT (12.9 vs. 16.2 years), had faster progression from PSC diagnosis to LT (2.5 vs. 4.1 years), and had higher alanine aminotransferase (112 vs. 66 IU/L) at LT (all P  < 0.01). Inflammatory bowel disease was more prevalent in the rPSC group (86% vs. 66%; P  = 0.025). After LT, rPSC subjects had more episodes of biopsy‐proved acute rejection (mean 3 vs. 1; P  < 0.001), and higher prevalence of steroid‐refractory rejection (41% vs. 20%; P  = 0.04). In those with rPSC, 43% developed complications of portal hypertension, were relisted for LT, or died within 2 years of the diagnosis. Mortality was higher in the rPSC group (11.1% vs. 2.9%; P  = 0.05). Conclusions: The incidence of rPSC in this cohort was higher than previously reported, and was associated with increased morbidity and mortality. Patients with rPSC appeared to have a more aggressive, immune‐reactive phenotype. These findings underscore the need to understand the immune mechanisms of rPSC, to lay the foundation for developing new therapies and improve outcomes in this challenging population.